Elliptical Polarization of Localized States in an Anisotropic Single GaAs Quantum Ring - Seongho Park; Minju Kim; Inhong Kim; Robert A. Taylor; Jindong Song; Kwangseuk Kyhm (Nanomaterials, 2022)
Localized states in an anisotropic single GaAs quantum ring were investigated in terms of polarization dependence of micro-photoluminescence spectrum at 5K. Given four Stokes parameters measured with a pair of linear polarizers and waveplates, the elliptical polarization states of two different vertical confinement states (<semantics>k=1</semantics> and <semantics>k=2</semantics>) were compared with phase, rotation, and ellipticity angles. While the polarized emission intensity of the <semantics>k=2</semantics> states becomes enhanced along [1,1,0] compared to that along [1,<semantics><mover>1¯</mover></semantics>,0], the polarization asymmetry of the <semantics>k=1</semantics> states shows the opposite result. We conclude the polarization state is determined by the shape of the lateral wavefunctions. In the <semantics>k=2</semantics> state, crescent-like wavefunctions are strongly localized, but the <semantics>k=1</semantics> state consists of two crescent-like wavefunctions, which are connected weakly through quantum tunneling.